Hypoxemia and Right-to-Left-Shunt in Patient with Antiphospholipid Syndrome: A Case Report with Multimodality Imaging Findings and Literature Review - Mnahi Bin Saeedan; Mashael Alrujaib; Ahmed L. Fathala (Case Reports in Radiology)
This is a case report of an extremely rare cause of superior vena cava syndrome with systemic-to-pulmonary venous shunts, illustrated using different imaging modalities with successful SVC and IVC dilatation and stenting.